Urinary Immune Complexes Reflect Renal Pathology in Lupus Nephritis - Chenling Tang; Aygun Teymur; Tianfu Wu (Diagnostics)
Background/Objectives: Lupus nephritis (LN) is a serious complication of systemic lupus erythematosus (SLE), involving immune complex deposition in the kidneys. While renal biopsy is the diagnostic gold standard, its invasiveness limits frequent use, driving the need for non-invasive urinary biomarkers to monitor disease progression and response to treatment. This study aimed to identify and validate urinary biomarkers for LN. Methods: Data from 10 LN-related omics databases, including urine, PBMCs, and kidney tissue, were analyzed. Differentially expressed proteins (DEPs) and genes (DEGs) were identified, and candidate biomarkers were validated via ELISA in an independent cohort of 87 urine samples. Results: We identified 78 biomarkers, with 14 overlapping across transcriptomic categories. Novel urinary biomarkers, including SERPING1, SLPI, and CD48, were validated. Urinary CD163, VCAM1, and ALCAM levels showed significant differences between LN and healthy controls, while urinary immune complexes (ICx) demonstrated superior diagnostic performance, with urinary ALCAM-ICx and CCL21-ICx achieving the highest AUC values. Conclusions: Our findings highlight the potential of urinary immune complexes and antigens as non-invasive biomarkers for LN. ALCAM, CD163, and SERPING1-ICx, in particular, were found as promising candidates for a urinary biomarker panel to aid in the diagnosis and monitoring of LN.